Vitamin D and calcium-phosphorus in serum of children with celiac disease in a zone of high sunlight exposure - Kamilova, Altinoy T.; Alieva, Nigora R.; Akhmedova, Dilorom I.; Abrorova, Barno T. (Frontiers in Pediatrics, 2025)
ActualityThe relationship between vitamin D levels and celiac disease (CeD) in children remains controversial. Uzbekistan is a country where the average number of sunny days is more than 300 days. There are few studies on the vitamin D status of children with celiac disease in an area of high insolation.Aim of the studyTo determine vitamin D status in children with CeD and to evaluate clinical and laboratory parameters in children depending on vitamin D levels.Patients and methodsWe examined 60 children with first diagnosed CeD aged from 1 to 16 years, the average age was 6 ± 2.3 years. The diagnosis was established on the basis of ESPGHAN 2012 criteria. In all children serum 25(OH)D, calcium, phosphorus, parathormone, alkaline phosphatase was determined. The control group consisted of 31 children of identical age.ResultsChildren with CeD had significantly lower mean serum 25(OH)D levels (14.8 ± 1.04 ng/ml) compared to controls (45.1 ± 8.04 ng/ml; p < 0.001). Vitamin D deficiency (<20 ng/ml) was identified in 80% of patients with CeD, including 25% with levels <10 ng/ml. Vitamin D insufficiency was observed in 20%. Lower vitamin D levels were associated with more pronounced clinical features suggestive of metabolic imbalance, including stunting and growth retardation (observed in 41.7% and 43.8% of cases, respectively). Bone deformations were more frequent in vitamin children with D deficiency, with a significant inverse correlation between vitamin D levels and clinical bone manifestations. Serum alkaline phosphatase and parathormone levels were significantly higher in children with vitamin D deficiency and insufficiency (p < 0.05, p < 0.001), with inverse correlations between vitamin D and these markers.ConclusionChildren with celiac disease living in a region with increased sun light exposure showed a high prevalence of vitamin D deficiency. In our study, vitamin D deficiency in patients with celiac disease was associated with more severe clinical manifestations.